Reduction of tinnitus severity by the centrally acting muscle relaxant cyclobenzaprine: An open-label pilot study - Coelho, Claudia (2012)
Tinnitus, the phantom perception of sounds, is a highly prevalent disorder. Although a wide variety of drugs have been investigated off label for the treatment of tinnitus, there is no approved pharmacotherapy. We report an open-label exploratory pilot study to assess the effect of muscle relaxants acting on the central nervous system on tinnitus patients. Cyclobenzaprine at high (30 mg) and low doses (10 mg), orphenadrine (100 mg), tizanidine (24 mg) and eperisone (50 mg) were administered to a maximum of 20 patients per group over a 12-week period. High-dose cyclobenzaprine resulted in a significant reduction in the Tinnitus Handicap Inventory (THI) score between baseline and week 12 in the intention-to-treat sample. On the other hand, other treatments were not effective. These results were confirmed in an explorative analysis where baseline corrected THI and Clinical Global Impression scores at week 12 were compared between groups. The present open trial presents a new promising pharmacotherapy for tinnitus that should be validated in placebo-controlled double-blind trials.